Strategi Komunikasi Pemanfaatan Varietas Unggul Baru Padi Toleran Rendaman - Herlina Tarigan; Rita Nur Suhaeti; Rudy Sunarja Rivai (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 2016)
Indonesia is still in struggle achieving sustainable food self-sufficiency, especially for rice. Rice production enhancement deals with many challenges, among others, negative impacts of climate change such as floods and droughts. Submergence tolerant rice varieties (STRV) invented by IAARD takes a relatively long time to be adopted by rice farmers. It needs an effective communication strategy to overcoming this situation. This paper identifies communication system in STRV dissemination process and acceptance while trying to formulate an effective communication strategy to speed up the adoption process to support food self-sufficiency achievement. Farmers’ rate of adoption of technology innovation was influenced by internal factors, external factors, socio-economic and environmental conditions. The research was conducted in 2015 on various types of lowland, that is, prone-flood irrigated lowland in West Java Province and in swamp tidal irrigated lowland and swampy irrigated lowland in South Kalimantan Province. The data were analyzed using both communication theory and institutional evaluation. SRTV socialization communication and adoption was a stratified communication linear model, directional, and no room for feedback. This system could only work effectively in a relatively long time such that the behavior change was slow. The system will be more effective in reaching early adopter groups and takes longer to spread to other recipient groups. An effective, equitable interactional communication model was required by setting up dialogues on each stage such that STRV adoption could be accelerated. Institutionally, STRV adoption required new breakthroughs because, in addition to technical problems, it was necessary to improve technology dissemination mechanism with better communication systems. AbstrakIndonesia terus berupaya mencapai swasembada pangan berkelanjutan, terutama untuk komoditas beras. Peningkatan produksi padi banyak menghadapi tantangan antara lain dampak negatif perubahan iklim seperti banjir dan kekeringan. Hasil penelitian Badan Litbang Pertanian yang potensial seperti varietas unggul baru padi toleran rendaman (VUB-PTR) seringkali lama diadopsi karena komunikasi dan strateginya kurang efektif. Tulisan ini bertujuan mengidentifikasi sistem komunikasi pada proses sosialisasi dan pemanfaatan VUB-PTR sekaligus mencoba merumuskan strategi komunikasi yang efektif untuk mempercepat proses adopsinya sehingga dapat mendukung pencapaian swasembada pangan. Tingkat penerimaan petani terhadap teknologi inovasi dipengaruhi oleh faktor internal, faktor eksternal, dan kondisi sosial ekonomi lingkungan. Penelitian dilaksanakan tahun 2015 pada berbagai tipe lahan sawah, yaitu lahan sawah irigasi rentan banjir di Provinsi Jawa Barat dan lahan rawa pasang surut dan rawa lebak di Provinsi Kalimantan Selatan. Analisis data menggunakan kombinasi teori komunikasi dengan analisis kelembagaan. Sistem komunikasi sosialisasi dan pemanfaatan VUB-PTR merupakan komunikasi berjenjang dengan model linier, sifatnya searah, dan tidak ada ruang untuk menyampaikan umpan balik. Sistem ini hanya bisa berjalan efektif dalam waktu relatif lama sehingga perubahan perilaku lambat. Sistem lebih efektif menjangkau kelompok pengguna awal dan membutuhkan waktu lebih lama untuk menyebar ke kelompok penerima lainnya. Diperlukan pembangunan sistem komunikasi yang lebih efektif dan setara model interaksional dengan membuka ruang dialog pada masing-masing tahapan sehingga adopsi inovasi bisa dipercepat. Secara kelembagaan, pemanfaatan VUB-PTR memerlukan terobosan baru karena selain persoalan teknis, perlu perbaikan mekanisme diseminasi teknologi dengan sistem komunikasi yang lebih baik.